PENGARUH EFIKASI DIRI, DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI KERJA SEBAGAI MEDIASI PADA BLPT YOGYAKARTA - Titien Nur Rachmawati; Prayekti Prayekti; Gendro Wiyono (Universitas Bina Taruna Gorontalo, 2024)
This research aims to determine and analyze the influence of self-efficacy, work discipline and work environment on employee performance at BLPT Yogyakarta which is mediated by work motivation. This research is a quantitative research with a survey method that takes samples from the entire population of 105 people and uses a questionnaire as the main data collection tool with a Likert scale. The sampling technique uses a saturated sample technique (census). The data analysis technique used is inner model with SmartPLS 3.2.9. The results of this research show that the impact that Self-Efficacy has on Employee Performance is shown by the Original Sample Coefficient (OS) value of 0.320 and the p-value of 0.000 is smaller than the 5% significance level (0.05) which indicates a significant effect. Work Discipline on Employee Performance is shown by the Original Sample Coefficient (OS) value of 0.400 and the p-value of 0.000 is smaller than the 5% significance level (0.05) which indicates a significant effect. Work Environment on Employee Performance is shown by the Original Sample Coefficient (OS) value of 0.295 and the p-value of 0.000 is smaller than the 5% significance level (0.05) which indicates a significant effect. It can be concluded that employee performance can be influenced by self-efficacy, work discipline and work environment.